Pioglitazone therapy in patients with stroke and prediabetes: a post hoc analysis of the IRIS randomized clinical trial - Spence, J. David; Viscoli, Catherine M.; Inzucchi, Silvio E.; Dearborn-Tomazos, Jennifer; Ford, Gary A.; Gorman, Mark; Furie, Karen L.; Lovejoy, Anne M.; Young, Lawrence H.; Kernan, Walter N.; Ringleb, Peter A. (JAMA neurology, 2019)
Importance In the Insulin Resistance Intervention After Stroke (IRIS) randomized clinical trial, pioglitazone, an insulin-sensitizing agent, reduced the risk for recurrent stroke or myocardial infarction (MI) among patients with insulin resistance. However, insulin resistance is not commonly measured in clinical practice. Objective To analyze the effects of pioglitazone in patients with good adherence as well as intention-to-treat effects of pioglitazone in patients with prediabetes in the IRIS trial. Design, Setting, and Participants The IRIS trial was a randomized multicenter clinical trial in patients with prior stroke or transient ischemic attack as well as insulin resistance but not diabetes. Patients were enrolled from February 2005 to January 2013, and the median follow-up was 4.8 years. The post hoc analyses reported here were performed from June to September 2018. Per American Diabetes Association criteria, prediabetes was defined as having a hemoglobin A1clevel of 5.7% to 6.4% or fasting plasma glucose level of 100 mg/dL to 125 mg/dL (to convert to mmol/L, multiply by 0.0555). Good adherence was defined as taking 80% or more of the protocol dose. Fasting glucose and hemoglobin A1c, used to define prediabetes, and adherence of 80% or higher, stipulated in the protocol as defining good adherence, were prespecified subgroups in the analysis plan. Interventions Participants were randomized to 15 mg of pioglitazone, with dose titrated to target of 45 mg daily, or matching placebo. Main Outcomes and Measures The primary outcome was recurrent stroke or MI. Secondary outcomes included stroke, acute coronary syndrome, stroke/MI/hospitalization for heart failure, and progression to diabetes. Results Among 3876 participants analyzed in the IRIS trial, 2885 were included in this analysis (1456 in the pioglitazone cohort and 1429 in the placebo cohort). The mean (SD) age of patients was 64 (11) years, and 974 (66.9%) and 908 (63.5%) of patients were men in the pioglitazone and placebo cohort, respectively. In the prediabetic population with good adherence (644 of 1456 individuals [44.2%] in the pioglitazone group and 810 of 1429 [56.7%] in the placebo group), the hazard ratios (95% CI) were 0.57 (0.39-0.84) for stroke/MI, 0.64 (0.42-0.99) for stroke, 0.47 (0.26-0.85) for acute coronary syndrome, 0.61 (0.42-0.88) for stroke/MI/hospitalization for heart failure, and 0.18 (0.10-0.33) for progression to diabetes. There was a nonsignificant reduction in overall mortality, cancer, and hospitalization, a slight increase in serious bone fractures, and an increase in weight gain and edema. Intention-to-treat results also showed significant reduction of events but to a lesser degree. Hazard ratios (95% CI) were 0.70 (0.56-0.88) for stroke/MI, 0.72 (0.56-0.92) for stroke, 0.72 (0.52-1.00) for acute coronary syndrome, 0.78 (0.63-0.96), for stroke/MI/hospitalization for heart failure, and 0.46 (0.35 to 0.61) for progression to diabetes. Conclusions and Relevance Pioglitazone may be effective for secondary prevention in patients with stroke/transient ischemic attack and with prediabetes, particularly in those with good adherence. Trial Registration ClinicalTrials.gov identifier:NCT00091949